Lactic acid bacteria (LAB) fermented soymilk exerted anti-inflammatory effects via suppression of inflammatory related cytokines and genes in Dextran Sulfate Sodium (DSS) induced colitis mice / Hanum Ya'akub - Ya'akub, Hanum (2014)
Ulcerative colitis (VC), a form of inflammatory bowel disease (IBD), is characterized by chronic inflammation of the colon. Its pathogenesis is associated with abnormal composition of the gut microflora. The use of probiotics, especially lactic acid bacteria (LAB), to improve gut microflora could thus serve as a good strategy in modulating inflammatory response during treatment of DC. As such, the principal aim of the present study was to identify LAB with potential anti-inflammatory effects against DC. For this purpose, 12 LAB isolated from Malaysian fermented food and dairy products were screened for their inhibitory effects against nitric oxide (NO), a known biomarker of DC using the Griess assay in vitro. The RAW 264.7 macrophages were cultured and served as the source of NO. Two LAB strains which elicited the most potent anti-NO activity, Pediococcus pentosaceus (LAB 8) and Lactobacillus plantarum (LAB 12), were then fermented in soymilk for validation of their anti-inflammatory effect in vivo. Colitis was induced in BALB/c mice (n = 12/ group) by administrating 3% DSS to drinking water for 7 days together with the LAB (10⁹ cfu/200 µl). Lactobacillus casei strain Shirota (LABPC) and sulfasalazine were used as reference strain and positive control, respectively. After 28 days of pretreatment with SM-LAB followed by 7 days of colitis induction, colons were removed for morphological examination before homogenised and being subjected to examination of gene expression (iNOS and NOD2) and physiological responses related to inflammation (NO, myeloperoxidase (MPO), lipid peroxidation and cytokines [tumor necrosis factor-a (TNF-a), interferon-y (IFN-y), interleukin 17A (IL-7A), interleukin 6 (IL-6), and interleukin 12 (IL-12)] levels). Preliminary in vitro screening found LAB 8 and LAB 12 to exhibit significant (p<O.05) NO inhibitory effect when compared to the rest of the LAB and the constitutive NO synthase (NOS) inhibitor, N-nitro-L-arginine methyl ester (L-NAME) which served as positive control. Subsequent in vivo study using mice with DSS-induced colitis continned the anti-inflammatory effects of 8M-LAB8 and SM-LAB12. The ability of SM-LAB8 and SM-LAB12 in reversing inflammation could be clearly observed morphologically from the histological analysis. Even though all groups administered by SM-LAB showed symptoms of less severe colitis as indicated by the percentage of weight loss, colon length and DAI scoring, only SM-LAB12 exhibited significant results (p<O.05). Furthermore, SM-LABI2 was also significantly (p<O.05) reduced concentrations of tested inflammatory markers which include NO, MPO, lipid peroxidation, TNF-a, IFN-y, IL-6, IL-12, and IL-17A. Generally, the anti-inflammatory outcomes resulted by SM-LAB (except lipid peroxidation) were better as opposed to 8M-LABPC. Both 8M-LAB8 and SM-LAB12 also demonstrated their ability in significantly (p<0.05) suppressing IBD associated genes, iNOS and NOD2 in the colitis mice model. In conclusion, the results suggest that consumption of LAB strains is able to inhibit several inflammatory markers and alleviates DC. Although LAB may offer as new therapeutic option, further experiments must be conducted to understand the exact mechanisms behind their action.